2013
DOI: 10.1111/jnc.12335
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coronin‐1a as a novel antibody target for clinically isolated syndrome and multiple sclerosis

Abstract: Recently, we identified the mimotope UH-CIS6 as a novel candidate antibody target for clinically isolated syndrome (CIS) and relapsing-remitting (RR) multiple sclerosis (MS). The purpose of this study was to further validate UH-CIS6 as an antibody target for CIS and MS and to identify the in vivo antibody target of UH-CIS6. First, a UH-CIS6 peptide ELISA was optimized. Next, we investigated the antibody response toward UH-CIS6 in cerebrospinal fluid (CSF) from patients with CIS (n = 20), MS (n = 43) and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Monoclonal antibodies against Coronin-1A are being investigated as potential therapy for human autoimmune diseases and lymphoid malignancies [8, 9]. Here we report a new seventh case of human Coronin-1A deficiency and review our patient’s findings in the context of current knowledge.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Monoclonal antibodies against Coronin-1A are being investigated as potential therapy for human autoimmune diseases and lymphoid malignancies [8, 9]. Here we report a new seventh case of human Coronin-1A deficiency and review our patient’s findings in the context of current knowledge.…”
Section: Introductionmentioning
confidence: 89%
“…Immunohistochemistry of brain samples from patients suffering from multiple sclerosis (MS) showed the presence of Coronin-1A expressing T cells and macrophages in active MS lesions, along with increased MHC class-II and reduced proteolipid protein [8]. Coronin-1A was recognized by MS patient cerebrospinal fluid (CSF) antibodies reactive to the peptide UH-CIS6 [49], suggesting Coronin-1A as a novel antibody target in the treatment of MS [8].…”
Section: Coronin-1a As a Therapeutic Target In Autoimmune And Autoactmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, elevated levels of autoantibodies have been reported in MS (29,30). In light of these findings, we investigated whether the T FR com-partment known to regulate humoral immunity is disturbed in MS. We show a decreased frequency of circulating T FR in MS patients (n = 172; for more information, see Supplemental Table I) compared with HCs (n = 107; for more information, see Supplemental Table I; p , 0.0001; Fig.…”
Section: Circulating T Fr Frequencies Are Decreased In Patients With Msmentioning
confidence: 97%
“…It has been reported that coronin-1a is required for the development of systemic lupus erythematosus (4). Recently, antibody reactivity toward coronin-1a has been observed in patients with multiple sclerosis (5), which is an autoimmune disease with large amount of activated T cells in the blood and cerebrospinal fluid (6)(7)(8). Meanwhile, in ankylosing spondylitis, immunosuppression therapy with sinomenine downregulates the expression of coronin-1a in peripheral blood mononuclear cells (PBMCs) (9).…”
Section: Coronin-1a Is a Potential Therapeutic Target For Activated Tmentioning
confidence: 99%